Language Assessment Literacy of Teachers - Weng, Fanrong; Shen, Bin (Frontiers in Psychology, 2022)
Language assessment literacy is a significant component of language teachers’ expertise but is also a challenging task for most language teachers. To date, there have been relatively few studies examining the research on language assessment literacy during these decades. To fill this void, this article reviews the conceptualizations of language assessment literacy and relevant empirical studies published from 1991 to 2021. It first analyzes various conceptualizations of language assessment literacy. Then in examining the empirical studies on language assessment literacy, five major themes emerge: i) teachers’ language assessment literacy levels; ii) factors influencing language assessment literacy; iii) language teachers’ assessment training needs, iv) language assessment training courses and v) language assessment literacy development through reflection. Finally, future research directions on teachers’ LAL are discussed.